1999
DOI: 10.1002/(sici)1097-0061(199910)15:14<1485::aid-yea477>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel vacuolar protein encoded bySSU21 /MCD4 is involved in cell wall integrity in yeast

Abstract: Using a screening procedure for obtaining yeast strains with enhanced ability to secrete heterologous protein, we have isolated a mutant with alteration of the cell wall structure. This mutant displayed strong decrease in cell wall mannoprotein content, which was not accompanied by decreased glycosylation of secreted proteins. The mutation defines a gene, designated SSU21(identical to previously characterized MCD4), which encodes a novel vacuolar protein. SSU21 is probably connected to the cell integrity prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 79 publications
(95 reference statements)
0
25
0
Order By: Relevance
“…Flury et al (1998) reported that Las21/ Gpi7 is localized to plasma membrane and Gaynor et al(1999) deduced the localization of Mcd4 at the ER from its amino acid sequence. By exploiting Mcd4-GFP fusion protein, Packeiser et al (1999) reported that Mcd4 was localized to the vacuolar membrane. Since the Mcd4-GFP construct lost some C-terminal amino acid residues including the ER retention signal, localization of Mcd4 should be reexamined experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…Flury et al (1998) reported that Las21/ Gpi7 is localized to plasma membrane and Gaynor et al(1999) deduced the localization of Mcd4 at the ER from its amino acid sequence. By exploiting Mcd4-GFP fusion protein, Packeiser et al (1999) reported that Mcd4 was localized to the vacuolar membrane. Since the Mcd4-GFP construct lost some C-terminal amino acid residues including the ER retention signal, localization of Mcd4 should be reexamined experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…Several mcd4 mutants had previously been labeled with [ 3 H]inositol but accumulated only very small amounts of Ins-labeled GPI lipids that could not be structurally analyzed (15,19,37). We therefore decided to analyze the in vitro GPI biosynthesis in yeast strains carrying either a temperature-sensitive mutation in MCD4/SSU21 (38) or the wild-type MCD4 gene under control of the GAL1 promoter (19). Microsomes from a wild-type strain make the complete GPI precursor CP2 irrespective of the carbon source on which cells have been grown (Fig.…”
Section: Addition Of Ethanolamine Phosphate To Man1mentioning
confidence: 99%
“…Yeast strains were S. cerevisiae W303-1B 15), 15 lys -⌬gpi8::kanMX containing plasmid YEpGPI8), FBY164 15 gpi8::kanMX2 ura3-1::URA3-GAL1,10 UAS -GPI8), RH932 (MATa gaa1 leu2 ura3 bar1-1) (Hamburger et al, 1995), 521-17A-H42 (MATa mcd4 trp1-289 leu2 ura3-52) (Packeiser et al, 1999), CWH4 (MAT␣ gpi1 ura3-52 lys2) (this mutant was isolated as cwh4 by Frans Klis; it is allelic to gpi1; I. Imhof, unpublished data), FBY656 15 lys -GPI8⌬::kanMX2 containing YCplac22-GST-GPI8), FBY733b (MATa his3⌬1 leu2⌬0 lys2⌬0 ura3⌬0 YHR188c::kanMX4 containing plasmid pYES2-GPI16), FBY735 (MATa his3⌬1 leu2⌬0 lys2⌬0 ura3⌬0 YHR188c::kanMX4 containing plasmid YCplac111-GAL1 UAS -GPI16), Y22882 (MATa/␣;his3⌬1/ his3⌬1;leu2⌬0/leu2⌬0;lys2⌬0/LYS2;MET15/met15⌬0;ura3⌬0/ura3⌬0;YHR188c::kanMX4/YHR188c, derived from BY4743, obtained from EUROSCARF), WADE060 -01A(A) (MATa ura3-1 his3-11 leu2-3,112 trp1⌬2 ade2-1 can1-100 YJR015w(-11, 1503)::kanMX4 in W303 background), and FBY91 (sec18 gpi8 -1 leu2). Yeast strains were cultured as previously described (Benghezal et al, 1996).…”
Section: Strains Growth Conditions and Materialsmentioning
confidence: 99%
“…As shown in Figure 11, Gpi8p remained completely confined within the complexes of 430 -650 kDa when prepro forms of GPI proteins were depleted with the use of cycloheximide, a treatment that was effective since it led to the complete disappearance of the immature 105-kDa form of the GPI protein Gas1p ( Figure 11B). The transamidase complex also persisted after a temperature shift of mutants that, upon a shift to 37°C, block the biosynthesis of GPI lipids at very early stages (gpi1 and mcd4) or interrupt the transfer of GPI lipids onto proteins (gaa1) (Hamburger et al, 1995;Leidich and Orlean, 1996;Gaynor et al, 1999;Packeiser et al, 1999). For gpi1, the efficiency of the block was assessed by following the gradual accumulation of the immature Gas1p ( Figure 2B).…”
Section: The Gpi High-molecular-weight Complex Persists In the Absencmentioning
confidence: 99%